The effects of β-Si3N4 whiskers and Fe–Cr–C alloy on the tribological properties of bronze matrix composites. (May 2021) - Pan, Jiaming; Yin, Jinwei; Xia, Yongfeng; Yao, Dongxu; Liang, Hanqin; Zuo, Kaihui; Zeng, Yuping
In order to improve the wear resistance, Fe–Cr–C alloy and β-Si3 N4 whiskers were chosen as the hard phases in bronze-graphite to prepare self-lubricating composite. Friction behaviors were tested with counter material 45# steel to evaluate the tribological properties of composites. The results indicated that Fe–Cr–C alloy and β-Si3 N4 whiskers played different roles in composites. β-Si3 N4 whiskers can obviously decrease the wear rate by excellent wear resistance. While the Fe–Cr–C alloy had better wettability with matrix, which improved the interfacial bonding and provided a continuous wear resistance. Moreover, Fe–Cr–C alloy also played a role in maintaining the friction coefficient stability, and this effect was more significant in the conditions of high rotational speeds. The composite containing 12.5 vol.% β-Si3 N4 whiskers and 2.5 vol.% Fe–Cr–C alloy in this research showed good friction performance.